Knowledge about tuberculosis, treatment adherence and outcome among ambulatory patients with drug-sensitive tuberculosis in two directly-observed treatment centres in Southwest Nigeria (2021)
Background: Tuberculosis (TB) remains one of the most common infectious diseases worldwide. Although TB is curable provided the treatment commenced quickly, appropriately and uninterrupted throughout TB treatment duration. However, high default rate, treatment interruption and therapy non-adherence coupled with inadequate disease knowledge significantly contribute to poor TB treatment outcome, especially in developing countries. This study therefore assessed knowledge about TB and possible reasons for treatment non-adherence among drugsensitive TB (DS-TB) patients, as well as evaluated treatment outcomes for the DS-TB managed within a 5-year period. Methods: A mixed-method design comprising a cross-sectional questionnaire-guided survey among 140-ambulatory DS-TB patients from January–March 2019, and a retrospective review of medical-records of DS-TB managed from 2013 to 2017 in two WHO-certified TB directly-observed-treatment centres. Data were summarized using descriptive statistics, while categorical variables were evaluated with Chi-square at p < 0.05. Results: Among the prospective DS-TB patients, males were 77(55.0%) and females were 63(45.0%). Most (63;45.0%) belonged to ages 18-34 years. A substantial proportion knew that TB is curable (137;97.9%) and transmittable (128; 91.4%), while 107(46.1%) accurately cited coughing without covering the mouth as a principal mode of transmission. Only 10(4.0%) mentioned adherence to TB medications as a measure to prevent transmission. Inaccessibility to healthcare facility (33;55.0%) and pill-burden (10,16.7%) were topmost reasons for TB treatment non-adherence. Of the 2262-DS-TB patients whose treatment outcomes were evaluated, 1211(53.5%) were cured, 580(25.6%) had treatment completed, 240(10.6%) defaulted, 54(2.3%) failed treatment and 177(7.8%) died. Overall, the treatment success rate within the 5-year period ranged from 77.4 to 81.9%.